2017
DOI: 10.1002/jsfa.8271
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological responses of different wheat genotypes to chilling stress: a cue to explain yield loss

Abstract: Diploid and tetraploid wheat genotypes maintained relatively large leaf area and high photosynthetic rates, but they were subjected to significant declines in vascular bundle number and productive tillers as a consequence of the inhibition by sink growth under chilling stress. The hexaploid wheats were found to have relatively low leaf area and photosynthetic rates. These genotypes also stored more soluble carbohydrates and exhibited stronger sink enhancement, ensuring the translocation and redistribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Blueberries are acid-loving soil plants, but high soil pH has been the primary abiotic stress factor limiting the growth of blueberry cultivation. Abiotic stress has adverse effects on plant phenotype, growth, biomass accumulation and yield (Holzapfel et al, 2004;Li et al, 2017;Sanoubar et al, 2020;Seleiman et al, 2021;Xu et al, 2022). Previous studies have shown that high soil pH levels cause iron deficiency and chlorosis in blueberry leaves, affect the absorption and transportation of mineral elements in plants, and inhibit plant growth and biomass accumulation (Jiang et al, 2017;Tamir et al, 2019;Tamir et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Blueberries are acid-loving soil plants, but high soil pH has been the primary abiotic stress factor limiting the growth of blueberry cultivation. Abiotic stress has adverse effects on plant phenotype, growth, biomass accumulation and yield (Holzapfel et al, 2004;Li et al, 2017;Sanoubar et al, 2020;Seleiman et al, 2021;Xu et al, 2022). Previous studies have shown that high soil pH levels cause iron deficiency and chlorosis in blueberry leaves, affect the absorption and transportation of mineral elements in plants, and inhibit plant growth and biomass accumulation (Jiang et al, 2017;Tamir et al, 2019;Tamir et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well‐documented that CS decreases grain yield in various crop plants (Rane et al, 2021; Ullah et al, 2022; Kuczyński et al, 2022; Li et al, 2022b; Bhat et al, 2022; Hernández et al, 2023), significantly impacting future food security for the growing population. For instance, CS at 13/8°C decreased maize yield by 21.87% (Waqas et al, 2017), while CS at 4°C decreased wheat yield by 40% (Li et al, 2017).…”
Section: Impact Of Climate Change and Extreme Temperature On Crop Pro...mentioning
confidence: 99%
“…It has been well documented that CS reduces yield percentage in different plants. For example, 40% wheat yield reduction was observed at 10/5 4 C [63], and 21.87% in maize at 13/8 C [64]. Under FS, in Bombax ceiba plants, a grain yield reduction of 3.3 and 8.4% at À14 and À17 C, respectively, were reported [65].…”
Section: Plant Responses To Temperature Stress: Development and Yieldmentioning
confidence: 99%